2017
DOI: 10.1186/s12889-017-4305-9
|View full text |Cite
|
Sign up to set email alerts
|

When communities are really in control: ethical issues surrounding community mobilisation for dengue prevention in Mexico and Nicaragua

Abstract: We discuss two ethical issues raised by Camino Verde, a 2011–2012 cluster-randomised controlled trial in Mexico and Nicaragua, that reduced dengue risk though community mobilisation. The issues arise from the approach adopted by the intervention, one called Socialisation of Evidence for Participatory Action. Community volunteer teams informed householders of evidence about dengue, its costs and the life-cycle of Aedes aegypti mosquitoes, while showing them the mosquito larvae in their own water receptacles, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Particularly stringent in randomized controlled trials where informed consent is a central concern, ethical codes play out very differently in conventional researcher‐led and in participatory research—where stakeholders essentially choose what they want to do . In participatory research, there are seldom concerns about placebos and issues of withholding interventions in controls can be settled by randomizing the delay among all eligible participants, as in a stepped wedge design.…”
Section: Ethics In Participatory Researchmentioning
confidence: 99%
“…Particularly stringent in randomized controlled trials where informed consent is a central concern, ethical codes play out very differently in conventional researcher‐led and in participatory research—where stakeholders essentially choose what they want to do . In participatory research, there are seldom concerns about placebos and issues of withholding interventions in controls can be settled by randomizing the delay among all eligible participants, as in a stepped wedge design.…”
Section: Ethics In Participatory Researchmentioning
confidence: 99%
“…We used the SEPA concept of "socialization of evidence for participatory action" to emphasize the importance of evidence-based discussions to motivate residents to take actions regarding vector control. 35,42,43 These discussions consisted of various forms of "chat" that residents have with each other and with nonparticipants (e.g., health officials and politicians) about the evidence of mosquito infestation that the brigadistas find. Participants used the term socializaci on for the in-person assembly they conducted after each session of house visits (Supplemental Figure 6); during the assembly, brigade members reported to each other what they found, how they related to residents, what problems they encountered, their assessment of neighborhood risk, and other information.…”
Section: Resultsmentioning
confidence: 99%
“…The potential of iNaturalist for detecting vector species was also verified in Europe, North America, North Africa and the Middle East [19], and the results indicated that the iNaturalist platform could complement existing vector surveillance data. Citizen science initiatives on mosquito surveillance are also emerging in tropical countries and areas where dengue and malaria are endemic [22,56,57], and ethical issues were discussed in a community-based program in Nicaragua and Mexico [58]. As ethical discussions underlining communitybased research have shown, researchers should ensure that individuals and communities have the autonomy to monitor and control the vectors in their properties and have a safe space for a dialogue focusing on mutual respect and community health [58].…”
Section: Discussionmentioning
confidence: 99%
“…Citizen science initiatives on mosquito surveillance are also emerging in tropical countries and areas where dengue and malaria are endemic [22,56,57], and ethical issues were discussed in a community-based program in Nicaragua and Mexico [58]. As ethical discussions underlining communitybased research have shown, researchers should ensure that individuals and communities have the autonomy to monitor and control the vectors in their properties and have a safe space for a dialogue focusing on mutual respect and community health [58]. Future studies regarding the utility of iNaturalist for public health should consider the ethical issues of vector surveillance in impoverished locations where diseases such as dengue and malaria are a major problem.…”
Section: Discussionmentioning
confidence: 99%